Composite negative electrode material and preparation method and application thereof
By using porous nanosilicon, carbon-containing resin, dopamine hydrochloride and graphite, a carbon layer with good conductivity is formed, which solves the problems of poor conductivity and low cycle stability of silicon-carbon composite materials in lithium-ion batteries, and achieves efficient electrochemical performance and simplified preparation process.
Patent Information
- Application Number
- CN202510098837.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The existing silicon-carbon composite materials have problems such as poor conductivity, low actual specific capacity, low cycle stability and complex preparation process in lithium-ion batteries.
The raw materials such as porous nanosilicon, carbon-containing resin, dopamine hydrochloride and graphite are used to form a carbon layer with good conductivity and a nitrogen-doped carbon layer through the heating and mixing process to enhance the conductivity and structural stability of the material.
The conductivity and electrochemical properties of composite negative electrode materials are improved, the structural stability of the material is enhanced, and the complexity and energy consumption of the preparation process are reduced.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite negative electrode material and a preparation method and application thereof. Background Art
[0002] As an emerging negative electrode material, silicon-carbon composite materials have attracted widespread attention in the field of lithium-ion batteries. Compared with traditional graphite negative electrode materials, silicon-carbon composite materials have higher theoretical capacity (up to 4200mAh / g), which makes them an ideal choice for the next generation of high-energy density lithium-ion batteries. However, in practical applications, although silicon-carbon composite negative electrodes have many advantages, their industrial application still faces some challenges. The preparation cost of silicon-carbon composite materials is high, and the cycle performance needs to be further improved, especially the cycle performance under high-rate charge and discharge conditions. In addition, the volume change of silicon-carbon composite materials is relatively large (up to 300%), which will lead to structural rupture of the material and decreased cycle performance. Furthermore, although carbon materials have good conductivity, the interface bonding force between silicon and carbon is relatively weak, and it is easy to form an interface layer with poor conductivity, which leads to an increase in the internal resistance of the battery and affects the charge and discharge performance of the battery; the preparation of silicon-carbon composite materials usually requires complex processes such as high-temperature sintering, mechanical ball milling, and chemical vapor deposition. These processes are not only energy-intensive, but also have high equipment costs and are difficult to mass produce. As an emerging negative electrode material for lithium-ion batteries, silicon-carbon composite materials have certain advantages in terms of specific capacity and cycle stability, but they still have problems such as poor conductivity, low actual specific capacity, cycle stability that needs to be improved, and complex preparation process. Summary of the invention
[0003] The present application provides a composite negative electrode material and a preparation method and application thereof, aiming to solve the problems of poor conductivity, low actual specific capacity, low cycle stability, and complex preparation process of existing carbon-silicon composite materials.
[0004] In a first aspect, the present application provides a composite negative electrode material, comprising the following raw materials in parts by mass: 3-8 parts of porous nano-silicon, 25-50 parts of carbon-containing resin, 0.8-1.4 parts of dopamine hydrochloride, and 5-15 parts of graphite.
[0005] According to some embodiments of the composite negative electrode material described in the present application, the carbon-containing resin includes one or more of an aqueous polyurethane resin, a phenolic resin, an epoxy resin, and polyacrylonitrile.
[0006] The second aspect of the present application provides a method for preparing the composite negative electrode material according to the first aspect of the present application, comprising the following steps:
[0007] (1) mixing and heating porous nano-silicon, a carbon-containing resin and a first solvent to obtain porous nano-silicon doped with conductive carbon;
[0008] (2) The porous nano-silicon, graphite, dopamine hydrochloride and a second solvent obtained in step (1) are mixed and heated to obtain the composite negative electrode material.
[0009] In the preparation method described in the present application, dopamine hydrochloride will polymerize on the surface of porous nano-silicon and graphite to form a polydopamine coating. This coating will carbonize at high temperature to form a carbon layer with good conductivity. At the same time, the doping of nitrogen elements can further improve the conductivity and electrochemical properties of the material. In addition, the introduction of polydopamine also enhances the bonding force between the materials and improves the structural stability of the materials.
[0010] During the high-temperature carbonization process, some pores of porous nanosilicon may be adjusted due to the formation of the carbon layer, making the pore distribution more reasonable, which is conducive to the penetration of electrolyte and the transmission of ions, thereby improving the electrochemical properties of the material.
[0011] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, the first solvent includes ethanol and / or methanol.
[0012] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, in step (1), the temperature of the mixed heating is 700-900° C., and the time of the mixed heating is 3-5 h.
[0013] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, in step (1), the heating rate of the mixed heating is 4-6°C / min.
[0014] According to some embodiments of the method for preparing a composite negative electrode material described in the present application, the second solvent includes methanol and / or ethanol.
[0015] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, in step (2), the temperature of the mixed heating is 700-900° C., and the time of the mixed heating is 2-4 hours.
[0016] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, in step (2), the heating rate of the mixed heating is 4-6°C / min.
[0017] According to some embodiments of the method for preparing a composite negative electrode material described in the present application, the mixing and heating in step (1) and step (2) are both performed under an inert atmosphere; preferably, the inert atmosphere includes an argon atmosphere and / or a nitrogen atmosphere.
[0018] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, the preparation of the porous nano-silicon comprises the following steps:
[0019] a. Mixing and heating triethylamine, hexadecyltrimethylammonium bromide, sodium salicylate, ethyl orthosilicate, 1,2-bis(triethoxysilyl)ethane and a third solvent, and performing a template removal treatment on the mixed heating product to obtain a porous nano-silicon material precursor;
[0020] b. Mixing hexadecyltrimethylammonium bromide, a porous nano-silicon material precursor and a fourth solvent to obtain porous nano-silicon.
[0021] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, the mass ratio of the triethylamine, the hexadecyltrimethylammonium bromide, the sodium salicylate, the ethyl orthosilicate and the 1,2-bis(triethoxysilyl)ethane is (1-3):(4-9):1:(2-6):(2-6).
[0022] According to some embodiments of the method for preparing a composite negative electrode material described in the present application, in step a, the temperature of the mixed heating is 70-90° C., and the time of the mixed heating is 12-16 hours.
[0023] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, in step a, the template removal treatment includes mixing the mixed heating product with hydrochloric acid and methanol, and reflux stirring for 20-26 hours to remove the template.
[0024] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, the third solvent includes methanol and hydrochloric acid.
[0025] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, the mass ratio of the hexadecyltrimethylammonium bromide to the porous nano-silicon material precursor is (3-8):3.
[0026] According to some embodiments of the method for preparing the composite negative electrode material described in the present application, in step b, the mixing temperature is 50-60° C., and the mixing time is 20-30 hours.
[0027] According to some embodiments of the method for preparing a composite negative electrode material described in the present application, the fourth solvent includes methanol and an aqueous sodium hydroxide solution.
[0028] According to some embodiments of the composite negative electrode material preparation method described in the present application, the preparation of the porous nano-silicon also includes using ammonium nitrate to precipitate the product of the mixture of hexadecyltrimethylammonium bromide, porous nano-silicon material precursor and the fourth solvent, and centrifugally separating to obtain the porous nano-silicon.
[0029] The third aspect of the present application provides a lithium-ion battery, comprising the composite negative electrode material described in the first aspect of the present application or the composite negative electrode material obtained by the preparation method described in the second aspect of the present application. DETAILED DESCRIPTION
[0030] The embodiments of the present invention are described in detail below, which are intended to explain the present invention but are not to be construed as limiting the present invention.
[0031] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0032] The embodiment of the present application provides a composite negative electrode material, comprising the following raw materials in parts by mass: 3-8 parts of porous nano-silicon, 25-50 parts of carbon-containing resin, 0.8-1.4 parts of dopamine hydrochloride and 5-15 parts of graphite.
[0033] The composite negative electrode material described in the present application has a stable structure and excellent electrochemical performance.
[0034] In some embodiments of the present application, the carbon-containing resin includes one or more of water-based polyurethane resin, phenolic resin, epoxy resin and polyacrylonitrile; the carbon source will be carbonized at high temperature to form a carbon material with good conductivity, and these carbon materials will be evenly dispersed in the pores of the porous nano-silicon, thereby giving the porous nano-silicon conductive properties.
[0035] The addition of dopamine hydrochloride can form a layer of polydopamine coating on the surface of porous nano-silicon and graphite through polymerization reaction, and then carbonize at high temperature to form a nitrogen-doped carbon layer, which enhances the conductivity and structural stability of the material.
[0036] The present application also provides a method for preparing the composite negative electrode material according to the first aspect of the present application, comprising the following steps:
[0037] (1) mixing and heating porous nano-silicon, a carbon-containing resin and a first solvent to obtain porous nano-silicon doped with conductive carbon;
[0038] (2) The porous nano-silicon, graphite, dopamine hydrochloride and a second solvent obtained in step (1) are mixed and heated to obtain the composite negative electrode material.
[0039] In the preparation method described in the present application, dopamine hydrochloride will polymerize on the surface of porous nano-silicon and graphite to form a polydopamine coating. This coating will carbonize at high temperature to form a carbon layer with good conductivity. At the same time, the doping of nitrogen elements can further improve the conductivity and electrochemical properties of the material. In addition, the introduction of polydopamine also enhances the bonding force between the materials and improves the structural stability of the materials.
[0040] During the high-temperature carbonization process, some pores of porous nanosilicon may be adjusted due to the formation of the carbon layer, making the pore distribution more reasonable, which is conducive to the penetration of electrolyte and the transmission of ions, thereby improving the electrochemical properties of the material.
[0041] In some embodiments of the present application, the first solvent includes ethanol and / or methanol.
[0042] In some embodiments of the present application, in step (1), the temperature of the mixed heating is 700-900°C, such as 700°C, 750°C, 800°C, 860°C, 900°C, etc., and the time of the mixed heating is 3-5h, such as 3h, 4h, 5h, etc. This heating temperature range can promote uniform dispersion and effective doping of conductive carbon in porous nano-silicon, and avoid high temperature damage to the material structure.
[0043] The heating temperature of 700-900℃ can ensure the decomposition and carbonization of the carbon source to form conductive carbon. In this process, the carbon source undergoes pyrolysis and carbonization reaction at high temperature to generate carbon material with conductive properties. This temperature range can ensure the carbonization process without causing excessive graphitization or burning of the carbon material due to excessive temperature. At a heating temperature of 700-900℃, the conductive carbon can be evenly dispersed in the pores of porous nano-silicon to form a porous nano-silicon composite material doped with conductive carbon. This composite material not only retains the original properties of porous nano-silicon, such as high specific surface area, porosity and good adsorption performance, but also gives the material new conductive properties.
[0044] If the heating temperature is too high, the structure of porous nano-silicon may be destroyed, such as pore collapse and reduction in specific surface area, thus affecting the performance and application effect of the material. Therefore, choosing a moderate heating temperature range of 700-900°C can achieve effective doping of conductive carbon while maintaining the good structure of porous nano-silicon.
[0045] In some embodiments of the present application, the heating rate of the mixed heating is 4-6°C / min, for example, 4°C / min, 5°C / min, 6°C / min, etc.
[0046] In some embodiments of the present application, the second solvent includes methanol and / or ethanol.
[0047] In some embodiments of the present application, in step (2), the temperature of the mixed heating is 700-900°C, for example, 700°C, 750°C, 800°C, 860°C, 900°C, etc., and the time of the mixed heating is 2-4h; for example, 2h, 3h, 4h, etc.
[0048] In some embodiments of the present application, in step (2), the heating rate of the mixed heating is 4-6°C / min; for example, 4°C / min, 5°C / min, 6°C / min, etc.
[0049] In some embodiments of the present application, the mixed heating in step (1) and step (2) are both performed under an inert atmosphere; preferably, the inert atmosphere includes an argon atmosphere and / or a nitrogen atmosphere.
[0050] In some embodiments of the present application, the preparation of the porous nano-silicon comprises the following steps:
[0051] a. Mixing and heating triethylamine, hexadecyltrimethylammonium bromide, sodium salicylate, ethyl orthosilicate, 1,2-bis(triethoxysilyl)ethane and a third solvent, and performing a template removal treatment on the mixed heating product to obtain a porous nano-silicon material precursor;
[0052] b. Mixing hexadecyltrimethylammonium bromide, a porous nano-silicon material precursor and a fourth solvent to obtain porous nano-silicon.
[0053] The method for preparing the porous nano-silicon described in the present application can accurately control the pore size, shape and distribution of the porous material, so that the obtained porous nano-silicon material has a high degree of order and uniformity.
[0054] In some embodiments of the present application, the mass ratio of the triethylamine, the hexadecyltrimethylammonium bromide, the sodium salicylate, the ethyl orthosilicate and the 1,2-bis(triethoxysilyl)ethane is (1-3):(4-9):1:(2-6):(2-6).
[0055] In some embodiments of the present application, in step a, the temperature of the mixed heating is 70-90°C, for example, 70°C, 75°C, 80°C, 85°C, 90°C, etc., and the time of the mixed heating is 12-16h, for example, 12h, 14h, 15h, 16h, etc.
[0056] In some embodiments of the present application, in step a, the template removal treatment comprises mixing the mixed heating product with hydrochloric acid and methanol, and refluxing and stirring for 20-26 hours to remove the template;
[0057] In some embodiments of the present application, the third solvent includes methanol and hydrochloric acid.
[0058] In some embodiments of the present application, the mass ratio of the hexadecyltrimethylammonium bromide to the porous nano-silicon material precursor is (3-8):3, for example, 3:3, 4:3, 5:3, 6:3, 8:3, etc.
[0059] In some embodiments of the present application, in step b, the mixing temperature is 50-60° C., and the mixing time is 20-30 h;
[0060] In some embodiments of the present application, the fourth solvent includes methanol and an aqueous sodium hydroxide solution.
[0061] In some embodiments of the present application, the preparation of the porous nano-silicon further comprises using ammonium nitrate to precipitate a mixture of hexadecyltrimethylammonium bromide, a porous nano-silicon material precursor and a fourth solvent, and centrifuging to obtain the porous nano-silicon.
[0062] An embodiment of the present application also provides a lithium-ion battery, comprising the composite negative electrode material described in the first aspect of the present application or the composite negative electrode material obtained by the preparation method described in the second aspect of the present application.
[0063] The technical solution of the present application is further described below in conjunction with specific embodiments.
[0064] Example 1
[0065] A method for preparing a composite negative electrode material comprises the following steps:
[0066] (1) Preparation of porous nano-silicon: 10 g triethylamine, 35 mL hexadecyltrimethylammonium bromide (CTAB), and 5 mL sodium salicylate (NaSal) were added to water and stirred at 80 °C for 2 h; 20 ml tetraethyl orthosilicate (TEOS) and 20 ml 1,2-bis(triethoxysilyl)ethane (BTES) were mixed in a ratio of 5:5 and dripped into the above solution, and stirred continuously at 80 °C for 12 h. The product was collected by centrifugation and washed with ethanol. The product was then dispersed in a 2M HCl and methanol solution (the volume ratio of hydrochloric acid to methanol was 1:1), refluxed and stirred for 24 h to remove the template, and finally the particles were dried at 55 °C to obtain a porous nano-silicon material precursor.
[0067] Mix 7.5g of hexadecyltrimethylammonium bromide with methanol, water and sodium hydroxide solution, add 7.5g of porous nano-silicon material precursor to the above mixture, and stir and react at 60°C for 20h. Add 50g of ammonium nitrate to the above reaction solution for precipitation, centrifuge, wash once with water, wash twice with ethanol, and disperse by ultrasound for 1h. Finally, dry the particles at 55°C to obtain porous nano-silicon;
[0068] (2) 3 g of the porous nano-silicon obtained in step (1), 40 g of an aqueous polyurethane resin and 45 ml of anhydrous ethanol were mixed, and the mixture was heated to 800° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept heated for 4 h. After the heating was completed, the mixture was naturally cooled to room temperature to obtain porous nano-silicon doped with conductive carbon;
[0069] (3) The porous nano-silicon doped with conductive carbon obtained in step (2) and 5 g of graphite are added to 50 ml of methanol, and ultrasonically dispersed for 2 h. Then 1.4 g of dopamine hydrochloride is added to the mixed solution. Under an argon atmosphere, the dried product is heated to 800° C. at a heating rate of 5° C. / min, and kept heated for 3 h to obtain the composite negative electrode material.
[0070] Example 2
[0071] The composite negative electrode material of Example 2 is different from that of Example 1 only in that the amounts of waterborne polyurethane resin and graphite added to the composite negative electrode material of Example 2 are different from those in Example 1.
[0072] The specific steps include:
[0073] (1) Preparation of porous nano-silicon: refer to the preparation method of porous nano-silicon in Example 1;
[0074] (2) 3 g of the porous nano-silicon obtained in step (1), 25 g of an aqueous polyurethane resin and 45 ml of anhydrous ethanol were mixed, and the mixture was heated to 800° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept heated for 4 h. After the heating was completed, the mixture was naturally cooled to room temperature to obtain porous nano-silicon doped with conductive carbon;
[0075] (3) The porous nano-silicon doped with conductive carbon obtained in step (2) and 15 g of graphite are added to 50 ml of methanol, and ultrasonically dispersed for 2 h. Then 1.4 g of dopamine hydrochloride is added to the mixed solution. Under an argon atmosphere, the dried product is heated to 800° C. at a heating rate of 5° C. / min, and kept heated for 3 h to obtain the composite negative electrode material.
[0076] Example 3
[0077] The composite negative electrode material of Example 3 is different from that of Example 1 only in that the amounts of waterborne polyurethane resin and graphite added to the composite negative electrode material of Example 3 are different from those in Example 1.
[0078] The specific steps include:
[0079] (1) Preparation of porous nano-silicon: refer to the preparation method of porous nano-silicon in Example 1;
[0080] (2) 3 g of the porous nano-silicon obtained in step (1), 50 g of an aqueous polyurethane resin and 45 ml of anhydrous ethanol were mixed, and the mixture was heated to 800° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept heated for 4 h. After the heating was completed, the mixture was naturally cooled to room temperature to obtain porous nano-silicon doped with conductive carbon;
[0081] (3) The porous nano-silicon doped with conductive carbon obtained in step (2) and 5 g of graphite are added to 50 ml of methanol, and ultrasonically dispersed for 2 h. Then 1.4 g of dopamine hydrochloride is added to the mixed solution. Under an argon atmosphere, the dried product is heated to 800° C. at a heating rate of 5° C. / min, and kept heated for 3 h to obtain the composite negative electrode material.
[0082] Example 4
[0083] The composite negative electrode material described in Example 4 is different from that in Example 1 only in that the amounts of waterborne polyurethane resin and graphite added to the composite negative electrode material described in Example 4 are different from those in Example 1.
[0084] The specific steps include:
[0085] (1) Preparation of porous nano-silicon: refer to the preparation method of porous nano-silicon in Example 1;
[0086] (2) 3 g of the porous nano-silicon obtained in step (1), 25 g of an aqueous polyurethane resin and 45 ml of anhydrous ethanol were mixed, and the mixture was heated to 800° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept heated for 4 h. After the heating was completed, the mixture was naturally cooled to room temperature to obtain porous nano-silicon doped with conductive carbon;
[0087] (3) The porous nano-silicon doped with conductive carbon obtained in step (2) and 10 g of graphite are added to 50 ml of methanol and ultrasonically dispersed for 2 h. Then 1.4 g of dopamine hydrochloride is added to the mixed solution. Under an argon atmosphere, the dried product is heated to 800° C. at a heating rate of 5° C. / min and kept heated for 3 h to obtain the composite negative electrode material.
[0088] Comparative Example 1
[0089] The difference between the composite negative electrode material in Comparative Example 1 and Example 1 is that graphite is not used for coating during the preparation of the composite negative electrode material in Comparative Example 1.
[0090] The specific steps include:
[0091] (1) Preparation of porous nano-silicon: refer to the preparation method of porous nano-silicon in Example 1;
[0092] (2) 3 g of the porous nano-silicon obtained in step (1), 40 g of the aqueous polyurethane resin and 45 ml of anhydrous ethanol were mixed, and the mixture was heated to 800° C. at a heating rate of 5° C. / min under an argon atmosphere, and kept heated for 4 h. After heating was completed, it was naturally cooled to room temperature to obtain porous nano-silicon doped with conductive carbon, i.e., the composite negative electrode material described in Comparative Example 1.
[0093] Comparative Example 2
[0094] The difference between the composite negative electrode material described in Comparative Example 2 and Example 1 is that the composite negative electrode material described in Comparative Example 2 is not doped with conductive carbon during the preparation process.
[0095] The specific steps include:
[0096] (1) Preparation of porous nano-silicon: refer to the preparation method of porous nano-silicon in Example 1;
[0097] (2) 5 g of the porous nano-silicon obtained in step (1) and 5 g of graphite were added to 50 ml of methanol and ultrasonically dispersed for 2 h. Then 1.4 g of dopamine hydrochloride was added to the mixed solution. Under an argon atmosphere, the dried product was heated to 800° C. at a heating rate of 5° C. / min and kept heated for 3 h to obtain the composite negative electrode material.
[0098] Study on the electrical properties of the composite negative electrode materials described in Examples 1-4 and Comparative Examples 1-2 of the present application
[0099] The composite negative electrode materials described in Examples 1-4 and Comparative Examples 1-2 were respectively assembled with positive electrode materials, electrolytes and separators to form lithium-ion batteries.
[0100] The test results are shown in Table 1:
[0101] Table 1
[0102] First charge and discharge efficiency (%) 500 cycles capacity retention rate (%) 6C rate performance Example 1 88.7% 96.77% 99.18% Example 2 88.5% 95.09% 99.04% Example 3 87.6% 94.89% 98.88% Example 4 88.1% 96.25% 99.15% Comparative Example 1 86.5% 92.89% 94.24% Comparative Example 2 86.2% 92.21% 93.75%
[0103] It can be seen from Table 1 that the electrochemical performance of the composite negative electrode materials obtained in Examples 1-4 of the present application is better than the electrochemical performance of the negative electrode materials obtained without graphite coating or conductive carbon doping.
[0104] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A composite negative electrode material, characterized in that: The invention comprises the following raw materials in parts by weight: 3-8 parts of porous nano silicon, 25-50 parts of carbon-containing resin, 0.8-1.4 parts of dopamine hydrochloride and 5-15 parts of graphite.
2. The composite negative electrode material according to claim 1, characterized in that: The carbon-containing resin includes one or more of waterborne polyurethane resin, phenolic resin, epoxy resin and polyacrylonitrile.
3. The method for preparing the composite negative electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) mixing and heating porous nano-silicon, a carbon-containing resin and a first solvent to obtain porous nano-silicon doped with conductive carbon; (2) The porous nano-silicon, graphite, dopamine hydrochloride and a second solvent obtained in step (1) are mixed and heated to obtain the composite negative electrode material.
4. The method for preparing the composite negative electrode material according to claim 3, characterized in that: The first solvent includes ethanol and / or methanol; And / or, in step (1), the temperature of the mixed heating is 700-900° C., and the time of the mixed heating is 3-5 h; And / or, in step (1), the heating rate of the mixed heating is 4-6°C / min.
5. The method for preparing the composite negative electrode material according to claim 3, characterized in that: The second solvent includes methanol and / or ethanol; And / or, in step (2), the temperature of the mixed heating is 700-900° C., and the time of the mixed heating is 2-4 h; And / or, in step (2), the heating rate of the mixed heating is 4-6°C / min; And / or, the mixing and heating in step (1) and step (2) are both carried out under an inert atmosphere; preferably, the inert atmosphere includes an argon atmosphere and / or a nitrogen atmosphere.
6. The method for preparing the composite negative electrode material according to claim 3, characterized in that: The preparation of the porous nano-silicon comprises the following steps: a. Mixing and heating triethylamine, hexadecyltrimethylammonium bromide, sodium salicylate, ethyl orthosilicate, 1,2-bis(triethoxysilyl)ethane and a third solvent, and performing a template removal treatment on the mixed heating product to obtain a porous nano-silicon material precursor; b. Mixing hexadecyltrimethylammonium bromide, a porous nano-silicon material precursor and a fourth solvent to obtain porous nano-silicon.
7. The method for preparing the composite negative electrode material according to claim 6, characterized in that: The mass ratio of the triethylamine, the cetyltrimethylammonium bromide, the sodium salicylate, the ethyl orthosilicate and the 1,2-bis(triethoxysilyl)ethane is (1-3):(4-9):1:(2-6):(2-6); And / or, in step a, the temperature of the mixed heating is 70-90° C., and the time of the mixed heating is 12-16 hours; And / or, in step a, the template removal treatment comprises mixing the mixed heating product with hydrochloric acid and methanol, and reflux stirring for 20-26 hours to remove the template; And / or, the third solvent includes methanol and hydrochloric acid.
8. The method for preparing the composite negative electrode material according to claim 6, characterized in that: The mass ratio of the hexadecyltrimethylammonium bromide to the porous nano-silicon material precursor is (3-8): 3; And / or, in step b, the mixing temperature is 50-60°C and the mixing time is 20-30h; And / or, the fourth solvent includes methanol and aqueous sodium hydroxide solution.
9. The method for preparing the composite negative electrode material according to claim 6, characterized in that: The preparation of the porous nano-silicon also includes using ammonium nitrate to precipitate a mixture of hexadecyltrimethylammonium bromide, a porous nano-silicon material precursor and a fourth solvent, and centrifugally separating the mixture to obtain the porous nano-silicon.
10. A lithium ion battery, characterized in that: The invention comprises the composite negative electrode material according to any one of claims 1 to 2 or the composite negative electrode material obtained by the preparation method according to any one of claims 3 to 9.
Citation Information
Patent Citations
Silicon-graphene-porous carbon composite electrode material as well as preparation method and application thereof
CN109638270A
Silicon-carbon composite material as well as preparation method and application thereof
CN116487577A
Porous silicon-based composite material and preparation and application thereof
CN116706065A
Porous silicon-carbon composite material, preparation method thereof and application of porous silicon-carbon composite material in secondary battery
CN117766742A
Hollow / porous silicon-based composite material and preparation method thereof
US20210273221A1